Centro De Asistencia Integral Para La Mujer - Ospina Arango, María Fernanda (Universidad Antonio Nariño, 2023)
Architecture is proposed as a helpful tool for mothers in the prison system and, women who live inside prisons accompanied by their children, It is also desired to help women victims of domestic abuse. A place of development is implemented, with the objective of guaranteeing learning and care for both the woman and the minor, ensuring better living conditions and well-being for each of them